Liability of Substitute Notary Whose Deeds Containing Forge Signatures - Juniar, Nadia Tasha; Sitabuana, Tundjung Herning (Journal of Law, Politic and Humanities, 2024)
Given that Indonesia is a country based on legal principles where nearly everything is intertwined to government agencies or the law, the role of Notaries in Indonesia become very necessary. Many people find it difficult to process documents or deeds, so in this case the role of a notary becomes crucial for the community. This causes notaries to become busy and get sick or tired, causing notaries request to take leave. During their leave, the Notary shall appoint a Substitute Notary as stated in the Law of The Republic of Indonesia Number 30 of 2004 on Office of Notary Public (Law on the Rules of Notary Profession). Substitute Notary is responsible in carrying out the duties and obligations of the Notary who is on leave. In carrying out their obligations Substitute Notary must obey the laws and regulations in Indonesia. However in verdict number: 395/Pdt.G/2011/PN.JKT.Sel a deed by Substitute Notary contains a forge signature which lead to question about the liability of Substitute Notary in the case. The research used a normative juridical research method and using secondary data sources. The results of this research proves that the Substitute Notary is indeed committed an unlawful act against the Plaintiff. This research is aims to find the liability of Substitute Notary whose deeds containing forge signatures.